2015
DOI: 10.1021/acs.jmedchem.5b00523
|View full text |Cite
|
Sign up to set email alerts
|

6-Substituted Sulfocoumarins Are Selective Carbonic Anhdydrase IX and XII Inhibitors with Significant Cytotoxicity against Colorectal Cancer Cells

Abstract: 6-Substituted sulfocoumarins bearing the carboxamido, trimethylammonium as well as the cyano and methoxy moieties with interesting inhibitory activity/selectivity against the tumor associated carbonic anhydrase (CA, EC 4.2.1.1) isoforms hCA IX and XII are reported. Moieties leading to the best inhibition were tert-butylcarboxamido, phenylcarboxamido, and 4-pyridylcarboxamido, with K(I) values of 2.1-8.1 nM. No inhibition of the off-target hCA II and I was observed. A number of these compounds were evaluated ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 91 publications
(71 citation statements)
references
References 64 publications
(35 reference statements)
0
67
0
Order By: Relevance
“…(i) According to our previous reports [40][41][42][43][44] , isoform hCA I was not or was poorly inhibited by sulfocoumarins 7-14. Compounds 8 and 11 are high micromolar inhibitors, whereas the remaining ones did not significantly inhibit the enzyme below 10 mm inhibitor concentration.…”
Section: Ca Inhibitionmentioning
confidence: 88%
See 3 more Smart Citations
“…(i) According to our previous reports [40][41][42][43][44] , isoform hCA I was not or was poorly inhibited by sulfocoumarins 7-14. Compounds 8 and 11 are high micromolar inhibitors, whereas the remaining ones did not significantly inhibit the enzyme below 10 mm inhibitor concentration.…”
Section: Ca Inhibitionmentioning
confidence: 88%
“…Many synthetic efforts have been made for the development of specific CAIs: in the last 15 years, in addition to the classical ''tail approach'' [10][11][12][13][14][15][16][17][25][26][27][28] which is mainly applied to classical sulfonamide inhibitors and their isosters, novel CAIs scaffolds have been also identified such as the polyamines 29 , phenols [30][31][32] , dithiocarbamates [33][34][35][36] , xanthates 37 , coumarins, thiocoumarins, 2-thioxocoumarins, coumarine oximes 4,38,39 . Sulfocoumarins are the latest CAI class identified and similarly to the coumarins showed the most selective inhibition profiles against the pathologically valuable CA isoforms 1,9,[40][41][42][43][44] . In analogy to coumarins, the substitution pattern at the sulfocoumarin scaffolds strongly influences the potency and selectivity profile against different hCA isoforms 1, [40][41][42][43][44] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Carbonic anhydrase inhibitors are divided into four groups: inorganic anions, sulfonamidebased compounds (sulphonamides, sulfanilamides, sulphamates, and their derivatives), phenols, and coumarins 105 . A sulfonamide CA9 inhibitor (SLC-0111) is presently in Phase I clinical trials 107 . It has been shown that simultaneous inhibition of both CA9 and CA12 has a greater impact than inhibition of each individually or even inhibition of HIF-a 105 .…”
Section: Carbonic Anhydrase 12 (Caxi)mentioning
confidence: 99%